Penggunaan Dongeng Interaktif sebagai Media Pengembangan Kognitif dan Sosial-Emosional Anak Usia Dini di PAUD Bajo Sayang, Nusa Tenggara Timur - Ryan Marina; Dimas Prasetya; Arditya Prayogi; Alif Adhar Amatullah; Keisha Kirania Safitri (Lembaga Pengembangan Kinerja Dosen, 2025)
Early Childhood Education is a fundamental phase in the formation of a child's character and basic skills. This period, known as the golden age, is crucial for providing appropriate stimulation so that all aspects of a child's development can develop optimally. The limited learning resources at the Bajo Sayang Early Childhood Education on Boleng Island, West Manggarai Regency, drove the need for innovative, simple yet meaningful learning media. This community service activity aims to implement interactive storytelling as a learning medium that can stimulate the cognitive and social-emotional aspects of early childhood. The implementation method used a participatory and interactive approach, where children are actively involved through questions and answers, emotional expression, and supporting activities such as singing and dancing. The results of the activity indicate that the interactive storytelling method can improve children's concentration and courage in expressing opinions. Furthermore, children also demonstrate a better understanding of basic emotions such as happiness, sadness, and anger, as well as increased empathy for the story characters.